CARDIO-PROTECTIVE EFFECT OF SILYMARIN AND ITS COMBINATION WITH ALLOPURINOL IN ISCHEMIA REPERFUSION INJURY USING ISOLATED PERFUSED RAT HEARTS - SHARMA RAJINDER; KAUR AMRINDER; KAUR BARINDERJIT (International Journal of Pharma and Bio Sciences, 2015)
Ischemia- reperfusion injury is one of the major cause of cardiovascular mortality and may lead to myocardial infarction, cardiac arrhythmias, and contractile dysfunction. The present study was designed to investigate the cardioprotective effect of Silymarin in ischemia reperfusion injury. Myocardial ischemia reperfusion injury was produced by mounting isolated rat hearts on Langendorff’s apparatus and global ischemia was produced for 30 min followed by reperfusion for 120 min. The animals were divided into six groups. In control group only global ischemia followed by reperfusion for 120 min was given. The standard groups received Allopurinol (50mg/L) and Silymarin (10mg/L) in vitro respectively. In treated groups, respective interventions Silymarin in different doses (2.5 mg/L, 5 mg/L and 10 mg/L) in combination with Allopurinol (50mg/L) were given. Myocardial infarct size was estimated macroscopically using TTC staining. The magnitude of cardiac injury was measured by lactate dehydrogenase and creatine kinase concentration in the coronary effluent. The increase in infarct size and the release of LDH and CK are documented to be an index of I/R induced myocardial injury. The results revealed that the Silymarin (10mg/L) significantly reduced ischemia-reperfusion induced myocardial injury in vitro. However, the combination of Silymarin and Allopurinol (10mg/L+ 50mg/L) prevented marked ischemia-reperfusion injury when compared with other combination assessed in terms of infarct size, release of LDH and CK level. Thus, it may be concluded that administration of a combination of Allopurinol and Silymarin may provide better cardioprotection by preventing ischemia and reperfusion injury in rat models.